Pollution of Diplodus Vulgris fish with Hydrocarbons on the shores of the Gulf of Ain El-Ghazala, Eastern of Libya - Sultana Moemen Hussein; Salma Fiasl Shallof; Hawa Mohammed El-Mesmary (Bani Waleed University Journal of Humanities and Applied Sciences, 2025)
The study was conducted to determine the extent of contamination of Diplodus vulgris fish with some hydrocarbon compounds (aromatic and aliphatic), in the waters of Ain Ghazala Bay. These fish were obtained from this site, and transferred from fishing sites in special boxes "Iceboxes" to the laboratory in the central laboratory of the Department of Food Science and Technology / Alexandria University / Shatby - Arab Republic of Egypt, where initial treatments and chemical analyses were carried out, then the concentration of hydrocarbon compounds was identified using the GC/Mass device. The concentration of these compounds in the fish was identified, as the results obtained showed that the percentage of hydrocarbon compounds in these fish was (0.68% and 32%) for aromatic and aliphatic compounds, respectively. Which poses a threat to human health.